Special Report: Active Offer of Services in French : The Cornerstone for Achieving the Objectives of Ontario's French Language Services Act (Ontario, 2016)
"This report will highlight the need for the Government of Ontario to put concrete measures in place and adopt the tools that are needed in order for government ministries, agencies and entitles, and third parties that provide services on behalf of the government to implement the active offer of services in French."--Executive summary